On the evaluation of interface quality in concrete repair system by means of impact-echo signal analysis. (1st March 2017) - Garbacz, Andrzej; Piotrowski, Tomasz; Courard, Luc; Kwaśniewski, Lesław
Highlights: Concrete substrate roughness and microcracking influence stress wave propagation. No relation between bond strength and amplitudes of frequency peaks in IE spectrum. Proposed FE model is useful for simulation of stress wave propagation in repair systems with different interface quality. Bond strength estimation with IE needs advanced signal analysis e.g. wavelet analysis. Abstract: According to Concrete Repair Manual as well as ACI 562-16 and European EN 1504-10 standards, a bond strength as a measure of adhesion is one the main feature of repair system necessary to be assessed. The most common laboratory and engineering method for bond strength evaluation is pull-off test. This is however a semi-destructive method that needs a repair in a place of measurement. Recently, the great interest in nondestructive techniques (NDT) development is noted. Impact-echo (IE) is considered as one of the most promising methods for this purpose. In this paper, the study on the usability the IE test based on frequency spectrum analysis for bond strength evaluation is analyzed. Both Finite Element Method (FEM) simulation and experimental tests were performed in order to obtain potential relations between IE frequency spectrum and parameters characterizing concrete substrate quality that may affect the final bond strength and the real value of pull-off bond strength measured on samples as well. It was concluded that the IE method can be a useful tool for interface quality and bond strength evaluations in concrete repair system. However, more complex signal analysis, e.g. wavelet analysis, should be considered in the future.